Hierarchical Macromolecular Structures: 60 Years after the Staudinger Nobel Prize I - Percec, Virgil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Advances in Polymer Science enjoys a longstanding tradition and good reputation in its community. Each volume is dedicated to a current topic, and each review critically surveys one aspect of that topic, to place it within the context of the volume. The volumes typically summarize the significant developments of the last 5 to 10 years and discuss them critically, presenting selected examples, explaining and illustrating the important principles, and bringing together many important references of primary literature. On that basis, future research directions in the area can be discussed. Advances in Polymer Science volumes thus are important references for every polymer scientist, as well as for other scientists interested in polymer science - as an introduction to a neighboring field, or as a compilation of detailed information for the specialist.
Keywords: Chemistry; Polymers; Surfaces (Physics).; Chemistry; Polymer Sciences; Condensed Matter Physics; Characterization and Evaluation of Materials